Allometry of the pyrophytic Aristida in fire‐maintained longleaf pine–wiregrass ecosystems. Issue 1 (10th January 2019) - Shearman, Timothy M.; Varner, J. Morgan; Robertson, Kevin; Hiers, J. Kevin
Abstract : Premise of the Study: Aboveground biomass (AGB) of herbaceous vegetation is a primary source of fuel in frequent surface fires that maintain grasslands, savannas, and woodlands. Methods for nondestructively estimating AGB are required to understand the mechanisms by which fuels affect fire behavior and the effects of time since the last burn. We developed allometric equations to estimate AGB in wiregrass ( Aristida beyrichiana / A. stricta ), a dominant bunchgrass in Pinus palustris ecosystems and a key species for ecological restoration. Methods: We collected wiregrass from North Carolina to Florida, across a range of time‐since‐last burn and site types. We tested 32 mixed effect models to see which predictors were best at predicting live, dead, and total AGB. We also examined how time since burn (TSB) affected the live‐to‐dead ratio (LDR) using regression. Key Results: Wiregrass AGB was found to increase with increasing latitude (relative to tussock volume), possibly due to an increase in precipitation, and was greater on more fertile clay soils and flatwoods than on sandy soils. The LDR decreased as a power function with TSB, resulting in rapid accumulation of dead, highly flammable, biomass in the fire‐free period. Conclusions: Greater biomass will support fires of higher intensity. Our models can be useful in the parameterization of future physics‐based models to predict fire behavior. Understanding the environmental variables that influence the allometry of wiregrass should help increase the precision of AGB estimates and the subsequent effects on fire behavior and effects on neighboring vegetation.